Diaphragm and preparation method thereof, battery and electric equipment
By using the base film structure of polymer materials and inorganic material particles in the lithium-ion battery separator, the problem of inconsistent wetting properties of electrolyte inside and on the surface of the separator is solved, and the circulation retention rate and safety of the battery are improved.
Patent Information
- Application Number
- CN202411549274.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-07
AI Technical Summary
The existing lithium-ion battery separators have inconsistent wetting properties of the electrolyte inside and on the surface, which affects the reliability and safety of the battery.
A base film composed of polymer material and inorganic material particles is used to form a polymer matrix, and the inorganic material particles are dispersed in the matrix to improve the overall wetting and liquid retention ability of the separator.
By improving the wetting properties of the separator and liquid retention ability, we ensure the smooth migration of ions during the charging and discharging of the battery, and improve the cycle retention rate and safety of the battery.
Smart Images

Figure CN119401057A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and more specifically, to a diaphragm and a preparation method thereof, a battery and an electrical device. Background Art
[0002] As an important component of lithium-ion batteries, the separator mainly plays the role of isolating the positive and negative electrodes and conducting lithium ions. In addition, the wettability of the separator has a significant impact on the reliability and safety of the battery.
[0003] In the related art, a ceramic coating is applied on the diaphragm to improve the electrolyte wettability of the diaphragm surface, but the wettability inside the diaphragm cannot be consistent with that of the surface layer.
[0004] Therefore, it is necessary to provide a new technical solution to solve the above technical problems. Summary of the invention
[0005] An object of the present invention is to provide a new technical solution for a diaphragm.
[0006] According to a first aspect of the present invention, a separator is provided, comprising a base film, wherein components of the base film include a polymer material and inorganic material particles, wherein the polymer material forms a polymer matrix, and the inorganic material particles are dispersed in the polymer matrix.
[0007] Optionally, calculated by weight, the ratio of the polymer material to the inorganic material particles is 99-90:1-10.
[0008] Optionally, the polymer includes polyolefin, and the polyolefin material includes at least one of polyethylene and polypropylene.
[0009] Optionally, the inorganic material particles are a first porous structure.
[0010] Optionally, the pore diameter of the pores in the first porous structure is 5nm to 100nm.
[0011] Optionally, the inorganic material particles are made of oxides and / or non-oxides.
[0012] Optionally, the oxide includes at least one of alumina, boehmite, silica, titanium dioxide, and zirconium dioxide;
[0013] And / or, the non-oxide includes at least one of magnesium hydroxide, calcium sulfate and magnesium sulfate.
[0014] Optionally, the polymer matrix is a porous membrane having a second porous structure.
[0015] Optionally, the polymer matrix comprises one or more of polyolefin, polyethylene terephthalate, and polyimide.
[0016] Optionally, the inorganic material particles are dispersed in the pores of the second porous structure.
[0017] Optionally, the pore size of the pores in the second porous structure is 5 nm to 100 nm, and the particle size of the inorganic material particles is 50 nm to 2000 nm.
[0018] Optionally, the components of the base film further include an antioxidant.
[0019] Optionally, an inorganic layer and / or an adhesive layer is provided on at least one side of the base film in the thickness direction.
[0020] According to a second aspect of the present application, a method for preparing a diaphragm is provided. The method comprises:
[0021] Mixing polymer material and inorganic material particles to obtain a mixed material;
[0022] The mixed material is prepared as a base film to obtain a diaphragm;
[0023] Wherein, the inorganic material particles are dispersed in a polymer matrix formed by the polymer material.
[0024] Optionally, the mixed material further includes a pore-forming agent, and the step of preparing the mixed material into a base film includes:
[0025] Casting the mixture into a ribbon;
[0026] extracting the pore former from the ribbon;
[0027] The extracted ribbon is washed and then heat-set to obtain a base film.
[0028] Optionally, the step of extracting the pore-forming agent in the ribbon comprises:
[0029] Extracting the pore-forming agent in the ribbon once;
[0030] Thinning the strip after the primary extraction to a preset thickness;
[0031] The pore-forming agent in the thinned ribbon is extracted again.
[0032] Optionally, the mixed material also includes a pore former and an antioxidant. Calculated by mass, the sum of the polymer material and the inorganic material particles is 100 parts, the ratio of the polymer material to the inorganic material particles is 99-90:1-10, the pore former is 100 to 600 parts, and the antioxidant is 0.2 to 10 parts.
[0033] According to a third aspect of the present application, a battery is provided. The battery comprises:
[0034] Positive electrode;
[0035] Negative electrode;
[0036] A diaphragm is provided between the positive electrode sheet and the negative electrode sheet, and the diaphragm is any of the diaphragms described above, or a diaphragm prepared by any of the diaphragm preparation methods described above.
[0037] According to a fourth aspect of the present application, an electrical device is provided, the electrical device comprising the above-mentioned battery.
[0038] According to one embodiment of the present application, the polymer matrix can ensure the strength of the diaphragm, the inorganic material particles can improve the wettability of the diaphragm to the electrolyte, and the inorganic material particles are dispersed in the polymer matrix, which can improve the consistency of the wettability of the base membrane surface and the exterior, further improve the liquid absorption rate and liquid retention capacity of the diaphragm, ensure the smooth migration of ions during the charging and discharging process of the battery, and thereby improve the cycle retention rate of the battery.
[0039] Further features and advantages of the present invention will become apparent from the following detailed description of exemplary embodiments of the present invention with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] The accompanying drawings, which are incorporated in and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, serve to explain the principles of the invention.
[0041] Figure 1 It is a schematic diagram of the structure of a diaphragm according to an embodiment of the present application.
[0042] Figure 2 It is a flow chart of a method for preparing a diaphragm according to one embodiment of the present application.
[0043] Description of reference numerals:
[0044] 100, diaphragm;
[0045] 10. Base film; 11. Inorganic material particles;
[0046] 20. Inorganic layer; 30. Adhesive layer. DETAILED DESCRIPTION
[0047] Various exemplary embodiments of the present invention will now be described in detail with reference to the accompanying drawings. It should be noted that the relative arrangement of components and steps, numerical expressions and numerical values set forth in these embodiments do not limit the scope of the present invention unless otherwise specifically stated.
[0048] The following description of at least one exemplary embodiment is merely illustrative in nature and is in no way intended to limit the invention, its application, or uses.
[0049] Technologies, methods, and equipment known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered as part of the specification.
[0050] In all examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.
[0051] It should be noted that like reference numerals and letters refer to similar items in the following figures, and therefore, once an item is defined in one figure, it need not be further discussed in subsequent figures.
[0052] like Figure 1 As shown, according to the first embodiment of the present application, a membrane 100 is provided, including a base membrane 10, wherein components of the base membrane 10 include a polymer material and inorganic material particles 11, wherein the polymer material forms a polymer matrix, and the inorganic material particles 11 are dispersed in the polymer matrix.
[0053] Specifically, the separator 100 is used to isolate the positive electrode and the negative electrode of the battery, which can prevent direct contact between the positive and negative electrodes, thereby avoiding the occurrence of internal short circuits in the battery, and can allow ions in the electrolyte (such as lithium ions, sodium ions, etc.) to pass through. The battery can be a soft-pack battery, and the soft-pack battery can be a lithium battery.
[0054] The diaphragm 100 mainly includes a base film 10, which can be made of a mixture containing a polymer material and inorganic material particles 11. After being made, the polymer material forms a polymer matrix, which serves as the main part of the base film 10, and the inorganic material particles 11 are dispersed in the polymer matrix formed by the polymer material as fillers. Among them, the polymer matrix can ensure the strength of the diaphragm 100, and the inorganic material particles 11 have good polarity and good electrolyte affinity, which can improve the wettability and diffusion rate of the diaphragm 100 to the electrolyte, thereby improving the liquid absorption rate and liquid retention capacity of the diaphragm 100, and ensuring the smooth migration of ions during the charging and discharging process of the battery.
[0055] In an embodiment of the present application, the inorganic material particles 11 are dispersed in a polymer matrix formed by a polymer material. The polymer matrix can ensure the strength of the diaphragm 100. The inorganic material particles 11 can improve the wettability of the diaphragm 100 to the electrolyte, as well as the consistency of the wettability of the surface and the exterior of the base film 10. The liquid absorption rate and liquid retention capacity of the diaphragm 100 can be improved, ensuring the smooth migration of ions during the charge and discharge process of the battery, thereby improving the cycle retention rate of the battery.
[0056] In one example, the ratio of the polymer material to the inorganic material particles 11 is 99-90:1-10 calculated by weight.
[0057] In this example, the mass ratio of the polymer material and the inorganic material particles 11 in the base film 10 is 99-90:1-10. For example, the mass ratio of the polymer material and the inorganic material particles 11 in the base film 10 can be 99:1, 98:2, 97:3, 96:4, 95:5, 94:6, 93:7, 92:8, 91:9, 90:10, etc. Within this range, the wettability and diffusion ability of the diaphragm 100 are good.
[0058] In one example, the polymer material includes polyolefin, and the polyolefin includes at least one of polyethylene and polypropylene.
[0059] In this example, the polymer material (i.e., high molecular weight polymer) is polyolefin, for example, the polyolefin can be composed of one or two of polyethylene and polypropylene. This arrangement makes the diaphragm 100 have a high mechanical strength, ensuring that the diaphragm 100 can remain stable during battery assembly and use, and makes the base film 10 have good thermal stability, ensuring that the base film 10 maintains the same performance within a certain temperature range, and makes the base film 10 processable by processes such as stretching, which can meet the battery's requirements for the diaphragm 100 and is easy to process.
[0060] In one example, the inorganic material particles 11 are a first porous structure.
[0061] Specifically, a part of the inorganic material particles 11 or all of the inorganic material particles 11 have a porous structure. This arrangement can further improve the liquid retention capacity of the separator 100, thereby improving the cycle stability and charge and discharge performance of the battery.
[0062] In one example, the pore size of the pores in the first porous structure is 5 nm to 100 nm.
[0063] It should be noted that if the pore size of the pores in the first porous structure is too small, it is not easy to improve the liquid retention capacity of the diaphragm 100; if the pore size of the pores in the first porous structure is too large, it is easy to cause the particle size of the inorganic material particles 11 to be too large, which is easy to affect the thickness of the diaphragm 100, thereby reducing the energy density of the battery. In this example, the pore size of the pores in the first porous structure is 5nm to 100nm, for example, the pore size of the pores in the first porous structure is 5nm, 10nm, 25nm, 50nm, 75nm and 100nm, etc., which can effectively improve the liquid retention capacity of the diaphragm 100, and at the same time, it can avoid the thickness of the diaphragm 100 being too large to reduce the energy density of the battery.
[0064] In one example, the inorganic material particles 11 are made of oxides and / or non-oxides.
[0065] In this example, the inorganic material particles 11 include the following:
[0066] Case 1: The inorganic material particles 11 are particles made of oxides;
[0067] Case 2: The inorganic material particles 11 are particles made of non-oxides;
[0068] Case 3: The inorganic material particles 11 are particles made of oxides and non-oxides.
[0069] In this example, both the oxide and the non-oxide have excellent thermal stability, and can maintain the structure unchanged when the battery is overheated, thereby ensuring the reliability of the diaphragm 100. The inorganic material particles 11 prepared by the above materials can improve the thermal shrinkage resistance of the diaphragm 100 and prevent the battery from thermal runaway at high temperatures. The inorganic material particles 11 prepared by the above materials can also improve the hardness and tensile strength of the diaphragm 100, thereby improving the structural stability and cycle stability of the battery. In addition, the inorganic material particles 11 prepared by the above materials have better chemical stability, which can prevent the diaphragm 100 material from reacting adversely with the electrolyte; the non-oxide has an extremely high melting point and can remain stable under extreme working conditions of the battery.
[0070] In one example, the oxide includes at least one of alumina, boehmite, silica, titania, and zirconium dioxide.
[0071] In this example, the oxide is one of aluminum oxide, boehmite, silicon dioxide, titanium dioxide, and zirconium dioxide, or the oxide is a mixture of two or more of aluminum oxide, boehmite, silicon dioxide, titanium dioxide, and zirconium dioxide. The inorganic material particles 11 are particles prepared from the above oxides, which can ensure the structural stability and cycle stability of the battery.
[0072] In one example, the non-oxide includes at least one of magnesium hydroxide, calcium sulfate, and magnesium sulfate.
[0073] In this example, the non-oxide is one of magnesium hydroxide, calcium sulfate, and magnesium sulfate, or the oxide is a mixture of two or more of magnesium hydroxide, calcium sulfate, and magnesium sulfate. The inorganic material particles 11 are particles prepared from the above non-oxides, which can ensure the structural stability and cycle stability of the battery.
[0074] Furthermore, the thickness of the base film 10 is 4 μm to 16 μm, that is, the thickness of the base film 10 can be 4 μm, 8 μm, 12 μm, 16 μm, etc. The specific thickness can be set according to actual needs and will not be described in detail in this embodiment.
[0075] In one example, the polymer matrix is a porous membrane having a second porous structure.
[0076] In this example, the second porous structure can provide sufficient migration channels for ions, allowing the ions to move between the positive and negative electrodes in a shorter distance, completing the ion migration during the charge and discharge process, and is conducive to the adsorption and retention of more electrolyte, ensuring that the ions in the electrolyte can migrate smoothly during the battery charge and discharge process, thereby ensuring the battery's charge and discharge efficiency and cycle stability.
[0077] Specifically, the polymer matrix includes one or more of polyolefin, polyethylene terephthalate, and polyimide.
[0078] In one example, at least a portion of the inorganic material particles 11 are dispersed in the pores of the second porous structure.
[0079] In this example, one or more inorganic material particles are distributed in part or all of the pores of the second porous structure, and the number of inorganic material particles can be 1 to 100, which can be determined according to the pore size of the pores of the second porous structure and the particle size of the inorganic material particles 11, and this embodiment will not be repeated. Such a design can increase the contact area between the inorganic material particles and the electrolyte, which helps to adsorb and retain more electrolyte, thereby ensuring that the ions in the electrolyte can migrate smoothly during the battery charging and discharging process, thereby improving the battery cycle retention rate.
[0080] In one example, the pore size of the pores in the second porous structure is 5nm to 100nm, that is, the pore size of the pores in the second porous structure can be 5nm, 20nm, 40nm, 60nm, 80nm and 100nm, etc., and the particle size of the inorganic material particles is 50nm to 2000nm, that is, the particle size of the inorganic material particles can be 50nm, 200nm, 600nm, 1000nm, 1500nm and 2000nm, etc.
[0081] In this example, the pore size of the pores in the second porous structure and the particle size of the inorganic material particles are within the above ranges, which can effectively improve the liquid retention capacity of the separator 100 .
[0082] In the present invention, the hole body may be circular, polygonal or other irregular shapes, and the hole diameter of the hole body may be the maximum radial dimension of the hole body.
[0083] In one example, the base film 10 further comprises an antioxidant.
[0084] In this example, the base film 10 contains an antioxidant (e.g., antioxidant 1010), which helps to improve the thermal stability of the separator 100 and prevent the battery from thermal runaway in the case of overheating, thereby improving the safety of the battery. The antioxidant reacts with free radicals to interrupt the chain growth of auto-oxidation and eliminate peroxy free radicals to prevent polymer degradation, thereby slowing down the aging process of the separator 100, thereby ensuring the safety of the battery.
[0085] In one example, the inorganic layer 20 and / or the adhesive layer 30 is disposed on at least one side of the base film 10 in the thickness direction.
[0086] Specifically, the base film 10 has a first side and a second side that are relatively arranged in the thickness direction. In this example, the first side and the second side of the base film 10 are both coated with an inorganic layer 20, which can be a porous ceramic layer. The side of the inorganic layer 20 facing away from the base film 10 is coated with a glue layer 30.
[0087] In this example, the inorganic layer 20 can further improve the wettability of the separator 100, thereby improving the cycle retention rate of the battery. The glue layer 30 can enhance the adhesion between the pole piece and the separator 100, improve the hardness and integrity of the battery cell, and improve the structural stability of the battery. In addition, the glue layer 30 can make the contact between the pole piece and the separator 100 closer, reduce the unevenness of the interface, thereby reducing the contact resistance inside the battery and improving the overall performance of the battery.
[0088] According to another embodiment of the present application, a method for preparing a diaphragm 100 is provided. Figure 2 As shown, the preparation method comprises:
[0089] S1, mixing polymer material and inorganic material particles 11 to obtain a mixed material;
[0090] S2, preparing the mixed material into a base film 10 to obtain a diaphragm 100;
[0091] Wherein, the inorganic material particles are dispersed in a polymer matrix formed by the polymer material.
[0092] In this example, in step S1, the polymer material includes polyolefin, and the polyolefin includes at least one of polyethylene and polypropylene. The material of the inorganic material particles 11 is oxide and / or non-oxide, the oxide includes at least one of aluminum oxide, boehmite, silicon dioxide, titanium dioxide, and zirconium dioxide, and the non-oxide includes at least one of magnesium hydroxide, calcium sulfate, and magnesium sulfate. During preparation, the above materials are mixed and stirred evenly. For example, the above materials can be put into a charging kettle and stirred evenly, and a mixed material is obtained after stirring evenly.
[0093] In step S2 , the above-mentioned mixed material can be used as a raw material to prepare the base film 10 . When the diaphragm 100 only includes the base film 10 , the prepared base film 10 is the desired diaphragm 100 .
[0094] The dosage of the above-mentioned raw materials is not limited here, and those skilled in the art can set it according to actual needs.
[0095] The preparation method is simple to operate. The diaphragm 100 prepared by the preparation method includes a base film 10. The components of the base film 10 include polymer materials and inorganic material particles 11. The inorganic material particles 11 are dispersed in a polymer matrix formed by the polymer material. The polymer matrix can ensure the strength of the diaphragm 100. The inorganic material particles 11 can improve the wettability of the diaphragm 100 to the electrolyte, thereby improving the liquid absorption rate and liquid retention capacity of the diaphragm 100, ensuring the smooth migration of ions during the charge and discharge process of the battery, and further improving the cycle retention rate of the battery.
[0096] In one example, the mixed material further includes a pore former, and the step of preparing the mixed material into a base film 10 includes:
[0097] S21, casting the mixture into a ribbon;
[0098] S22, extracting the pore-forming agent in the ribbon;
[0099] S23, washing the extracted strip and performing heat setting treatment to obtain a base film 10.
[0100] In this example, the mixture also includes an antioxidant and a pore former, for example, the antioxidant is antioxidant 1010, and the pore former is liquid paraffin. In step S21, the mixture is continuously added to the twin-screw extruder, under heating conditions, for example, the heating temperature can be 170° C. to 230° C., and the polymer material can be in a molten state at this temperature. Under this condition, the mixture is extruded through a slit die to a casting cooling roller to cast the mixture into a strip.
[0101] Furthermore, the speed of the twin-screw extruder for extruding the composite material is 150 to 250 rpm. The cooling temperature during the tape casting is between 70°C and 90°C.
[0102] In step S22, the ribbon is placed in an extraction tank containing dichloromethane to extract the pore-forming agent in the ribbon, thereby achieving the purpose of pore formation.
[0103] In step S23, the temperature for heat setting the strip is 115°C to 125°C, and the heat setting time is 15 minutes to 25 minutes. Heat setting the strip can effectively improve the crystallinity and orientation of the polymer molecular chain. At the heat setting temperature, the polymer molecular chain obtains enough energy to rearrange, so that it is arranged more regularly, thereby improving the crystallinity and improving the tensile strength of the diaphragm 100. And the heat setting treatment of the strip can reduce the degree of thermal shrinkage of the diaphragm 100 and improve its dimensional stability at high temperature.
[0104] The diaphragm 100 prepared by this example has a polymer matrix formed by a polymer material that is a porous membrane. The porous membrane can provide sufficient migration channels for ions, allowing ions to move between the positive and negative electrodes at a shorter distance, completing the ion migration during the charge and discharge process, and is conducive to the adsorption and retention of more electrolyte, ensuring that the ions in the electrolyte can migrate smoothly during the battery charge and discharge process, thereby ensuring the battery's charge and discharge efficiency and cycle stability.
[0105] In one example, the step of extracting the pore former in the ribbon comprises:
[0106] S221, extracting the pore-forming agent in the ribbon once;
[0107] S222, thinning the strip after the first extraction to a preset thickness;
[0108] S223, extracting the pore-forming agent in the thinned ribbon again.
[0109] In this example, the pore-forming agent in the ribbon can be extracted multiple times. For example, in S221, the ribbon can be placed in an extraction tank containing an extraction liquid (for example, dichloromethane) to extract the pore-forming agent in the ribbon for the first time. It should be noted that the extraction liquid is compatible with the material of the pore-forming agent, and this example will not be repeated one by one.
[0110] In S222, the strip can be thinned by stretching, and specifically, a stretching machine, such as a bidirectional stretching machine, can be used to stretch and thin the extracted strip to a preset thickness under heating conditions. Bidirectional refers to the length direction and width direction of the strip. Thinning the strip by stretching can straighten the chain segments of the polymer material, so that the diaphragm 100 has higher strength in both the length direction and the width direction, and the diaphragm 100 has good performance in multiple directions. And thinning the strip by stretching can effectively control the number and size of pores on the base film 10, which is conducive to the preparation of the desired diaphragm 100.
[0111] Since the pore-forming agent that has not been extracted in the strip is exposed after the diaphragm 100 is thinned, in S223, the thinned strip can be placed in an extraction tank containing an extraction liquid to perform a second extraction on the pore-forming agent in the strip, so that the pore-forming agent that has not been extracted for the first time can be extracted to increase the number of pores in the base membrane 10.
[0112] Furthermore, the stretching ratio of the ribbon is 1.5×1.5 times to 12×12 times.
[0113] In one example, the mixed material also includes a pore former and an antioxidant. Calculated by mass, the sum of the polymer material and the inorganic material particles 11 is 100 parts, the ratio of the polymer material to the inorganic material particles 11 is 99-90:1-10, the pore former is 100 to 600 parts, and the antioxidant is 0.2 to 10 parts.
[0114] In this example, the mass fractions of the polymer material, the inorganic material particles 11, the pore former and the antioxidant are within the above ranges, and a membrane 100 having good mechanical strength, wettability and diffusion ability can be prepared.
[0115] The following is a performance comparison between the diaphragm 100 and the battery cell prepared in the embodiment of the present application and the diaphragm and the battery cell prepared in the comparative example.
[0116] Example 1
[0117] A mixture of 100g of ultra-high molecular weight polyethylene powder and porous inorganic material particles (95g of ultra-high molecular weight polyethylene powder, 5g of porous alumina, the average pore size of the porous alumina mesoporous body is 25nm), 250g of liquid paraffin and 0.5g of antioxidant 1010 are placed in a feeding kettle and stirred evenly at a stirring speed of 50 rpm to obtain a mixed material; the mixed material is continuously added to a twin-screw extruder, extruded at a speed of 200 rpm by the twin-screw extruder at 180°C, and extruded to a casting cooling roller through a slit die; cast into a strip at a temperature of 80°C; the obtained strip is placed in an extraction tank containing dichloromethane for extraction; the extracted strip is sent to a biaxial stretching machine at 120°C to be stretched into a film; the stretched strip is placed in an extraction tank containing dichloromethane for secondary extraction, and washed after completion. Heat setting at 120°C for 15 minutes to obtain a diaphragm.
[0118] The above-mentioned separator, LCO positive electrode and graphite negative electrode are wound, injected with liquid, aged and formed to obtain a battery cell.
[0119] Example 2
[0120] A mixture of 100g of ultra-high molecular weight polyethylene powder and porous inorganic material particles (92g of ultra-high molecular weight polyethylene powder, 8g of porous alumina, the average pore size of the porous alumina mesoporous body is 25nm), 250g of liquid paraffin and 0.5g of antioxidant 1010 are placed in a feeding kettle and stirred evenly at a stirring speed of 50 rpm to obtain a mixed material; the mixed material is continuously added to a twin-screw extruder, extruded at 180°C by the twin-screw extruder at a speed of 200 rpm, and extruded to a casting cooling roller through a slit die; cast into a strip at a temperature of 80°C; the obtained strip is placed in an extraction tank containing dichloromethane for extraction; the extracted strip is sent to a biaxial stretching machine at 120°C to be stretched into a film; the stretched strip is placed in an extraction tank containing dichloromethane for secondary extraction, and washed after completion. Heat setting at 120°C for 15 minutes to obtain a diaphragm.
[0121] The above-mentioned separator, LCO positive electrode and graphite negative electrode are wound, injected with liquid, aged and formed to obtain a battery cell.
[0122] Example 3
[0123] A mixture of 100g of ultra-high molecular weight polyethylene powder and porous inorganic material particles (for example, 90g of ultra-high molecular weight polyethylene powder, 10g of porous alumina, the average pore size of the porous alumina mesoporous body is 25nm), 250g of liquid paraffin and 0.5g of antioxidant 1010 are placed in a feeding kettle and stirred evenly at a stirring speed of 50 rpm to obtain a mixed material; the mixed material is continuously added to a twin-screw extruder, extruded at 180°C by the twin-screw extruder at a speed of 200 rpm, and extruded to a casting cooling roller through a slit die; cast into a strip at a temperature of 80°C; the obtained strip is placed in an extraction tank containing dichloromethane for extraction; the extracted strip is sent to a biaxial stretching machine at 120°C to be stretched into a film; the stretched strip is placed in an extraction tank containing dichloromethane for secondary extraction, and washed after completion. Heat setting at 120°C for 15 minutes to obtain a diaphragm.
[0124] The above-mentioned separator, LCO positive electrode and graphite negative electrode are wound, injected with liquid, aged and formed to obtain a battery cell.
[0125] Example 4
[0126] A mixture of 100g of ultra-high molecular weight polyethylene powder and porous inorganic material particles (for example, 92g of ultra-high molecular weight polyethylene powder, 8g of porous alumina, the average pore size of the porous alumina mesoporous body is 10nm), 250g of liquid paraffin and 0.5g of antioxidant 1010 are placed in a feeding kettle and stirred evenly at a stirring speed of 50 rpm to obtain a mixed material; the mixed material is continuously added to a twin-screw extruder, extruded at 180°C by the twin-screw extruder at a speed of 200 rpm, and extruded to a casting cooling roller through a slit die; cast into a strip at a temperature of 80°C; the obtained strip is placed in an extraction tank containing dichloromethane for extraction; the extracted strip is sent to a biaxial stretching machine at 120°C to be stretched into a film; the stretched strip is placed in an extraction tank containing dichloromethane for secondary extraction, and washed after completion. Heat setting at 120°C for 15 minutes to obtain a diaphragm.
[0127] The above-mentioned separator, LCO positive electrode and graphite negative electrode are wound, injected with liquid, aged and formed to obtain a battery cell, with LCO as the positive electrode and graphite as the negative electrode.
[0128] Example 5
[0129] A mixture of 100g of ultra-high molecular weight polyethylene powder and porous inorganic material particles (for example, 92g of ultra-high molecular weight polyethylene powder, 8g of porous alumina, the average pore size of the porous alumina mesoporous body is 50nm), 250g of liquid paraffin and 0.5g of antioxidant 1010 are placed in a feeding kettle and stirred evenly at a stirring speed of 50 rpm to obtain a mixed material; the mixed material is continuously added to a twin-screw extruder, extruded at 180°C by the twin-screw extruder at a speed of 200 rpm, and extruded to a casting cooling roller through a slit die; cast into a strip at a temperature of 80°C; the obtained strip is placed in an extraction tank containing dichloromethane for extraction; the extracted strip is sent to a biaxial stretching machine at 120°C to be stretched into a film; the stretched strip is placed in an extraction tank containing dichloromethane for secondary extraction, and washed after completion. Heat setting at 120°C for 15 minutes to obtain a diaphragm.
[0130] The above-mentioned separator, LCO positive electrode and graphite negative electrode are wound, injected with liquid, aged and formed to obtain a battery cell.
[0131] Example 6
[0132] A mixture of 100g of ultra-high molecular weight polyethylene powder and porous inorganic material particles (for example, 92g of ultra-high molecular weight polyethylene powder, 8g of porous silica, the average pore size of the porous silica mesoporous body is 25nm), 250g of liquid paraffin and 0.5g of antioxidant 1010 are placed in a feeding kettle and stirred evenly at a stirring speed of 50 rpm to obtain a mixed material; the mixed material is continuously added to a twin-screw extruder, extruded at 180°C by the twin-screw extruder at a speed of 200 rpm, and extruded to a casting cooling roller through a slit die; cast into a strip at a temperature of 80°C; the obtained strip is placed in an extraction tank containing dichloromethane for extraction; the extracted strip is sent to a biaxial stretching machine at 120°C to be stretched into a film; the stretched strip is placed in an extraction tank containing dichloromethane for secondary extraction, and washed after completion. Heat setting at 120°C for 15 minutes to obtain a diaphragm.
[0133] The above-mentioned separator, LCO positive electrode and graphite negative electrode are wound, injected with liquid, aged and formed to obtain a battery cell.
[0134] Example 7
[0135] A mixture of 100g of ultra-high molecular weight polyethylene powder and porous inorganic material particles (for example, 92g of ultra-high molecular weight polyethylene powder, 8g of porous magnesium hydroxide, the average pore size of the porous magnesium hydroxide mesoporous body is 25nm), 250g of liquid paraffin and 0.5g of antioxidant 1010 are placed in a feeding kettle and stirred evenly at a stirring speed of 50 rpm to obtain a mixed material; the mixed material is continuously added to a twin-screw extruder, extruded by the twin-screw extruder at a speed of 200 rpm at 180°C, and extruded to a casting cooling roller through a slit die; cast into a strip at a temperature of 80°C; the obtained strip is placed in an extraction tank containing dichloromethane for extraction; the extracted strip is sent to a biaxial stretching machine at 120°C to be stretched into a film; the stretched strip is placed in an extraction tank containing dichloromethane for secondary extraction, and washed after completion. Heat setting at 120°C for 15 minutes to obtain a diaphragm.
[0136] The above-mentioned separator, LCO positive electrode and graphite negative electrode are wound, injected with liquid, aged and formed to obtain a battery cell.
[0137] Example 8
[0138] A mixture of 100g of ultra-high molecular weight polyethylene powder and porous inorganic material particles (for example, 99g of ultra-high molecular weight polyethylene powder, 1g of porous alumina, the average pore size of the porous alumina mesopores is 25nm), 250g of liquid paraffin and 0.5g of antioxidant 1010 are placed in a feeding kettle and stirred evenly at a stirring speed of 50 rpm to obtain a mixed material; the mixed material is continuously added to a twin-screw extruder, extruded at 180°C by the twin-screw extruder at a speed of 200 rpm, and extruded to a casting cooling roller through a slit die; cast into a strip at a temperature of 80°C; the obtained strip is placed in an extraction tank containing dichloromethane for extraction; the extracted strip is sent to a biaxial stretching machine at 120°C to be stretched into a film; the stretched strip is placed in an extraction tank containing dichloromethane for secondary extraction, and washed after completion. Heat setting at 120°C for 15 minutes to obtain a diaphragm.
[0139] The above-mentioned separator, LCO positive electrode and graphite negative electrode are wound, injected with liquid, aged and formed to obtain a battery cell.
[0140] Example 9
[0141] A mixture of 100g of ultra-high molecular weight polyethylene powder and porous inorganic material particles (for example, 95g of ultra-high molecular weight polyethylene powder, 5g of porous alumina, the average pore size of the porous alumina mesoporous body is 5nm), 250g of liquid paraffin and 0.5g of antioxidant 1010 are placed in a feeding kettle and stirred evenly at a stirring speed of 50 rpm to obtain a mixed material; the mixed material is continuously added to a twin-screw extruder, extruded by the twin-screw extruder at a speed of 200 rpm at 180°C, and extruded to a casting cooling roller through a slit die; cast into a strip at a temperature of 80°C; the obtained strip is placed in an extraction tank containing dichloromethane for extraction; the extracted strip is sent to a biaxial stretching machine at 120°C to be stretched into a film; the stretched strip is placed in an extraction tank containing dichloromethane for secondary extraction, and washed after completion. Heat setting at 120°C for 15 minutes to obtain a diaphragm.
[0142] The separator 100, LCO positive electrode, and graphite negative electrode are wound, injected, aged, and formed to obtain a battery cell.
[0143] Example 10
[0144] A mixture of 100g of ultra-high molecular weight polyethylene powder and porous inorganic material particles (for example, 95g of ultra-high molecular weight polyethylene powder, 5g of porous alumina, the average pore size of the porous alumina mesoporous body is 100nm), 250g of liquid paraffin and 0.5g of antioxidant 1010 are placed in a feeding kettle and stirred evenly at a stirring speed of 50 rpm to obtain a mixed material; the mixed material is continuously added to a twin-screw extruder, extruded at 180°C by the twin-screw extruder at a speed of 200 rpm, and extruded to a casting cooling roller through a slit die; cast into a strip at a temperature of 80°C; the obtained strip is placed in an extraction tank containing dichloromethane for extraction; the extracted strip is sent to a biaxial stretching machine at 120°C to be stretched into a film; the stretched strip is placed in an extraction tank containing dichloromethane for secondary extraction, and washed after completion. Heat setting at 120°C for 15 minutes to obtain a diaphragm.
[0145] The above-mentioned separator, LCO positive electrode and graphite negative electrode are wound, injected with liquid, aged and formed to obtain a battery cell.
[0146] Comparative Example 1
[0147] 100g of ultra-high molecular weight polyethylene powder, 250g of liquid paraffin and 0.5g of antioxidant 1010 were put into a feeding kettle and stirred evenly at a stirring speed of 50 rpm to obtain a mixed material; the mixed material was continuously added to a twin-screw extruder, extruded at 180°C by the twin-screw extruder at a speed of 200 rpm, and extruded to a casting cooling roller through a slit die; cast into a strip at a temperature of 80°C; the obtained strip was placed in an extraction tank containing dichloromethane for extraction; the extracted strip was sent to a biaxial stretching machine at 120°C to be stretched into a film; the stretched strip was placed in an extraction tank containing dichloromethane for secondary extraction, and washed after completion. Heat-set at 120°C for 15 minutes to obtain a diaphragm.
[0148] The above-mentioned separator, LCO positive electrode and graphite negative electrode are wound, injected with liquid, aged and formed to obtain a battery cell.
[0149] It should be noted that the test method for the electrolyte wettability of the diaphragm is as follows: the diaphragm is cut into strips of 10 mm wide and 20 cm long, and both ends are fixed and hung horizontally on a bracket. 25 μL of electrolyte is added, and after 3 minutes, the diffusion length of the electrolyte on the diaphragm is measured.
[0150] The cycle performance test method is: at 25°C, charge to 4.45V at 1.5C, cut off at 0.02C, leave for 5 minutes, discharge to 3.0V at 0.7C, leave for 5 minutes, and repeat for 800 cycles. Record the discharge capacity, and the capacity retention rate is the ratio of the discharge capacity after 800 cycles to the initial capacity.
[0151] Table 1: Performance test table of the separator 100 and the battery of Examples 1 to 6 of the present application and the separator 100 and the battery of Comparative Example 1
[0152]
[0153] As shown in Table 1, the separator 100 of the present application containing the inorganic material particles 11 with a porous structure has the characteristics of strong electrolyte diffusion and good cycle retention rate.
[0154] According to another embodiment of the present application, a battery is provided. The battery may be a soft-pack battery, such as a lithium-ion roll core battery, and the battery includes: a positive electrode sheet, a negative electrode sheet, and a separator 100, wherein the separator 100 is disposed between the positive electrode sheet and the negative electrode sheet, and the separator 100 is the separator 100 described in any of the above embodiments, or the separator 100 prepared by the method for preparing the separator 100 described in any of the above embodiments.
[0155] Since the diaphragm 100 and the method for preparing the diaphragm 100 according to the embodiment of the present application have the above-mentioned technical effects, the battery according to the embodiment of the present application also has corresponding technical effects, which will not be described in detail in this embodiment.
[0156] According to another embodiment of the present application, an electric device is provided, which includes but is not limited to a vehicle, and the battery of any of the above embodiments of the electric device.
[0157] Since the diaphragm 100 and the method for preparing the diaphragm 100 according to the embodiment of the present application have the above-mentioned technical effects, the electrical equipment according to the embodiment of the present application also has corresponding technical effects, which will not be described in detail in this embodiment.
[0158] The above embodiments focus on the differences between the various embodiments. As long as the different optimization features between the various embodiments are not contradictory, they can be combined to form a better embodiment. Considering the simplicity of the text, they will not be repeated here.
[0159] Although some specific embodiments of the present invention have been described in detail by way of example, it will be appreciated by those skilled in the art that the above examples are for illustration only and are not intended to limit the scope of the present invention. It will be appreciated by those skilled in the art that the above embodiments may be modified without departing from the scope and spirit of the present invention. The scope of the present invention is defined by the appended claims.
Claims
1. A diaphragm, characterized in that: The invention comprises a base film, the components of which include a polymer material and inorganic material particles, the polymer material forms a polymer matrix, and the inorganic material particles are dispersed in the polymer matrix.
2. The diaphragm according to claim 1, characterized in that Calculated by mass, the ratio of the polymer material to the inorganic material particles is 99-90:1-10.
3. The diaphragm according to claim 1, characterized in that The polymer material includes polyolefin, and the polyolefin includes at least one of polyethylene and polypropylene.
4. The diaphragm according to claim 1, characterized in that The inorganic material particles have a first porous structure.
5. The diaphragm according to claim 4, characterized in that The pore size of the pores in the first porous structure is 5nm-100nm.
6. The diaphragm according to claim 1, characterized in that The inorganic material particles are made of oxides and / or non-oxides.
7. The diaphragm according to claim 6, characterized in that The oxide includes at least one of alumina, boehmite, silicon dioxide, titanium dioxide, and zirconium dioxide; And / or, the non-oxide includes at least one of magnesium hydroxide, calcium sulfate and magnesium sulfate.
8. The diaphragm according to claim 1, characterized in that The polymer matrix is a porous membrane having a second porous structure.
9. The diaphragm according to claim 1, characterized in that The polymer matrix includes one or more of polyolefin, polyethylene terephthalate, and polyimide.
10. The diaphragm according to claim 8, characterized in that At least a portion of the inorganic material particles are dispersed in the pores of the second porous structure.
11. The diaphragm according to claim 10, characterized in that The pore size of the pores in the second porous structure is 5nm-100nm, and the particle size of the inorganic material particles is 50nm-2000nm.
12. The diaphragm according to claim 1, characterized in that The components of the base film also include an antioxidant.
13. The diaphragm according to claim 1, characterized in that An inorganic layer and / or an adhesive layer is provided on at least one side of the base film in the thickness direction.
14. A method for preparing a diaphragm, characterized in that: include: Mixing polymer material and inorganic material particles to obtain a mixed material; The mixed material is prepared as a base film to obtain a diaphragm; Wherein, the inorganic material particles are dispersed in a polymer matrix formed by the polymer material.
15. The method for preparing a diaphragm according to claim 14, characterized in that: The mixed material further includes a pore-forming agent, and the step of preparing the mixed material into a base film includes: Casting the mixture into a ribbon; extracting the pore former from the ribbon; The extracted strip is washed and then heat-set to obtain a base film.
16. The method for preparing a diaphragm according to claim 15, characterized in that: The step of extracting the pore-forming agent in the ribbon comprises: Extracting the pore-forming agent in the ribbon once; Thinning the strip after the primary extraction to a preset thickness; The pore-forming agent in the thinned ribbon is extracted again.
17. The method for preparing a diaphragm according to claim 14, characterized in that: The mixed material also includes a pore former and an antioxidant. Calculated by mass, the sum of the polymer material and the inorganic material particles is 100 parts, the ratio of the polymer material to the inorganic material particles is 99-90:1-10, the pore former is 100 to 600 parts, and the antioxidant is 0.2 to 10 parts.
18. A battery, characterized in that: include: Positive electrode; Negative electrode; A diaphragm, wherein the diaphragm is disposed between the positive electrode sheet and the negative electrode sheet, and the diaphragm is the diaphragm according to any one of claims 1 to 13, or the diaphragm prepared by the diaphragm preparation method according to any one of claims 14 to 17.
19. An electrical equipment, characterized in that: Comprising the battery of claim 18.
Citation Information
Patent Citations
Preparation method of lithium-ion polyolefin membrane
CN103022401A
Ceramic diaphragm for lithium ion battery and preparation method of ceramic diaphragm
CN105514328A
Production method for battery separator
CN106058123A
Preparation method for battery diaphragm with three kinds of microporous structures
CN106328866A
Composite ceramic porous lithium battery diaphragm, preparation method and application of composite ceramic porous lithium battery diaphragm
CN108832064A